To solve \( f(3) - f^{-1}(5) - 2f^{-1}(3) \), we first need to look up the values in the given table:
\[ \begin{array}{c|c} x & f(x) \ \hline -7 & 5 \ -3 & 1 \ 3 & 9 \ 5 & 3 \ 9 & -4 \ \end{array} \]
-
Finding \( f(3) \): From the table, \( f(3) = 9 \).
-
Finding \( f^{-1}(5) \): We look for \( x \) such that \( f(x) = 5 \). From the table, we see that \( f(-7) = 5 \). Thus, \( f^{-1}(5) = -7 \).
-
Finding \( f^{-1}(3) \): We look for \( x \) such that \( f(x) = 3 \). From the table, we find that \( f(5) = 3 \). Therefore, \( f^{-1}(3) = 5 \).
Now we can substitute these values into the expression:
\[ f(3) - f^{-1}(5) - 2f^{-1}(3) = 9 - (-7) - 2 \times 5 \]
Calculating this step by step:
-
Calculate \( 9 - (-7) \): \[ 9 + 7 = 16 \]
-
Calculate \( 2 \times 5 \): \[ 2 \times 5 = 10 \]
-
Now substitute back into the expression: \[ 16 - 10 = 6 \]
Thus, the final result is:
\[ \boxed{6} \]